Analisis Semantik dan Semiotik Shalawat"Astagfirullah Robbal Baroya": Kajian Makna, Simbol - Tsalis Lutfi Sa'diyah; Siti Hanifah Amaliah; Nabila Aulia; Panni Adibah; Tria Nursyifa (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
This study examines the semantic and symbolic meanings embedded in the lyrics of the shalawat (Islamic devotional song) "Astagfirullah Robbal Baroya," while simultaneously analysing the internalisation of the Sufi values of khauf (fear of Allah) and raja' (hope for Allah's mercy) as represented therein. Employing a qualitative descriptive approach anchored in three complementary theoretical frameworks Geoffrey Leech's (1981) semantic theory, Charles Sanders Peirce's (1931–1958) triadic semiotics, and Abu Hamid al-Ghazali's concept of ahwal (spiritual states) in Ihya' 'Ulum al-Din the study systematically analyses nine key lexemes and phrases in the shalawat text. Findings reveal that the lyrical structure exhibits a patterned spiritual architecture: the opening stanzas are dominated by symbols actualising khauf through confessions of sin and acknowledgement of Allah's omnipotence, whilst the middle and closing stanzas express raja' through supplications for mercy and invocations of Allah's compassionate names. The integration point between the two values is identified in the phrase tawbatan nasuha, which semantically and semiotically carries both khauf and raja' simultaneously. The study demonstrates that shalawat functions not merely as devotional expression but as a structured sign system that internalises two fundamental Sufi values into the spiritual consciousness of its reader or listener.